2011
DOI: 10.1128/jvi.02426-10
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Herpes Simplex Virus to the Spinal Cord Is Independent of Spread to Dorsal Root Ganglia

Abstract: Levels of herpes simplex virus 1 (HSV-1) and HSV-2 DNA in dorsal root ganglia (DRG) and spinal cord (SC) were quantified after inoculation of guinea pig genitals and footpads. In genital infection, viral DNA reached SC and DRG simultaneously (at 2 to 3 days after inoculation) but was more abundant in SC than in DRG. After inoculation of footpads, which lack parasympathetic innervation, the viruses spread more efficiently to DRG than to SC. These results show important differences between genital and footpad in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…N, nuclear. lated, and both can establish latency in sensory ganglia and recurrently reactivate to cause diseases, but they exhibit substantial differences in latency and reactivation patterns (75). A large number of studies have demonstrated that HSV-1 evolved multiple countermeasures to subvert the production of type I IFNs (67,71,(76)(77)(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…N, nuclear. lated, and both can establish latency in sensory ganglia and recurrently reactivate to cause diseases, but they exhibit substantial differences in latency and reactivation patterns (75). A large number of studies have demonstrated that HSV-1 evolved multiple countermeasures to subvert the production of type I IFNs (67,71,(76)(77)(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…While recent evidence suggests the presence of latent genomes in autonomic tissues, 55 as well as within sensory neuron cell bodies, there is no evidence to date that non-replicating viral DNA can persist within keratinocytes or other non-neural tissues. For this reason, we believe that detection of a newly initiated HSV DNA shedding episode in the genital tract implies recent HSV replication in, and transport from, neuronal ganglia.…”
Section: Latency and Reactivationmentioning
confidence: 99%
“…Upon reactivation, the virus travels anterograde, exiting the axons to replicate in the periphery. There is ample evidence that the virus also infects and establishes latency in peripheral autonomic ganglia, potentially giving rise to autonomic symptoms during acute infection (10)(11)(12)(13)(14)(15)(16), and HSV-1 can be induced to reactivate from autonomic ganglia by neurectomy (17), but spontaneous reactivation via autonomic pathways has not yet been demonstrated.…”
mentioning
confidence: 99%
“…During acute infection of guinea pigs, typical human autonomic symptoms, such as urinary retention, may also be observed. Rapid but independent spread of acutely infecting virus both to DRG and spinal cord (SC) suggests that the virus may spread to the SC via nonsensory (e.g., autonomic) neuronal pathways (15). In guinea pigs with latent HSV-2 ocular infection, immediate early and early genes were detected in sympathetic superior cervical ganglia, while only immediate early genes were found in parasympathetic ciliary ganglia.…”
mentioning
confidence: 99%